Detection of the CTX-M Gene Associated with Extended-Spectrum β-Lactamase (ESBL) in Broiler Chickens in Surabaya Traditional Markets - Putri, Mariana Febrilianti Resilinda; Khairullah, Aswin Rafif; Effendi, Mustofa Helmi; Wibisono, Freshinta Jellia; Hasib, Abdullah; Moses, Ikechukwu Benjamin; Fauziah, Ima; Kusala, Muhammad Khaliim Jati; Raissa, Ricadonna; Yanestria, Sheila Marty (Jurnal Medik Veteriner, 2024)
A common indicator used to examine the frequency and distribution of antibiotic resistance against other enteric bacteria in humans and animals is the commensal enteric bacterium, Escherichia coli. The transmission of plasmids harboring ESBL enzymes, primarily generated by E. coli, is the cause of this resistance. The purpose of this study was to identify the CTX-M gene in ESBL-producing E. coli from broiler chicken cloacal swabs in traditional Surabaya markets. The samples used were 96 cloacal swabs from broiler chickens in the traditional markets of Dukuh Kupang, Keputran, Pacar Keling, and Pucang. The antibiotic disks used in this study belonged to five different antibiotic classes; they are aztreonam (monobactam), chloramphenicol (phenicol), kanamycin (aminoglycoside), ciprofloxacin (fluoroquinolone), and tetracycline (tetracycline). Presumptive ESBL strains were then molecularly screened for the presence of CTX-M gene. Results revealed that out of the 96 chicken cloacal swab samples collected, 58 (60.42%) were positive for E. coli based on morphological culture, Gram staining, and biochemical tests. Additionally, 15 out of the 58 E. coli isolates recovered from broiler chicken cloacal swabs were multidrug-resistant (MDR) while 7 of E. coli isolates harbored CTX-M gene. Conclusively, this study has shown that broiler chickens sold in traditional Surabaya markets harbor MDR E. coli which possess CTX-M gene. Conditions in traditional markets with low levels of cleanliness and chickens placed close together can spread resistance genes with serious public health consequences. Therefore, it is imperative to observe good hygienic practices in Surabaya traditional markets in order to curtail the spread of MDR bacterial pathogens in the food chain.